Effect of Anaerobiosis on Expression of Virulence Factors in Vibrio cholerae - Krishnan, H. H. (American Society for Microbiology, 2004)
In Vibrio cholerae, the transmembrane DNA binding proteins, ToxR and TcpP, activate expression of the regulatory gene toxT in response to specific environmental signals. The resulting enhanced level of ToxT leads to a coordinated increase in the production of a subset of virulence factors, including cholera toxin (CT) and toxin-coregulated pilus (TCP). The effect of anaerobiosis on expression of the V. cholerae virulence regulatory cascade was examined. The expression of the major regulatory genes, tcpP, toxR, and toxT, in anaerobically grown V. cholerae was comparable to that in cells grown under aerobic conditions, and no significant difference in the ToxT-dependent expression of tcpA was detected when aerobic and anaerobic cultures were compared. However, in spite of the presence of functional ToxT, ctxAB expression was drastically reduced, and practically no CT was detected in cells grown under anaerobic conditions. In a V. cholerae hns mutant, however, high levels of ctxAB expression occurred even under anaerobic conditions. Also, deletion of the H-NS binding site from the ctxAB promoter eliminated anaerobic repression of ctxAB expression. These results suggest that H-NS directly represses ctxAB expression under anaerobic growth conditions. It has been reported that in the first stage of infection of infant mice by V. cholerae, tcpA is expressed but ctxAB expression is shut off (S. H. Lee, D. L. Hava, M. K. Waldor, and A. Camilli, Cell 99: 625-634, 1999). This pattern is similar to the pattern in anaerobic cultures of V. cholerae. Under all other in vitro conditions, ctxAB and tcpA are known to be coordinately expressed.